Characterization of patients with thoracic trauma treated at the Enrique Cabrera Hospital. 2014-2018 - Jorge Agustín Satorre Rocha; Olga Caridad León González; Pedro Rolando López Rodriguez; Eduardo García Castillo; Luis Manuel Danta Fundora (Medisur)
Foundation: thoracic trauma is common in today's society and of great importance due to the nature of the organs that are located within it. Objective: to characterize patients with thoracic trauma treated at the Enrique Cabrera Hospital. Methods: descriptive, retrospective research, in which 102 patients who were admitted to Enrique Cabrera Hospital with the diagnosis of thoracic trauma were studied, from January 1, 2014 to December 31, 2018. The variables analyzed were: age, sex, cause and type of trauma, type of injury, treatment, complications and hospital stay. Results: prevalence of the male sex (77.45%) and the 40 to 49 year old group (25, 49%). Traffic accidents were the most frequent cause of trauma (31, 38%); Bruising thoracic trauma prevailed (63.73%). The most frequent thoracic lesion was pneumothorax (44, 11%) and the most observed extrathoracic lesions occurred in the extremities (13, 72%); no lesions were associated in 66.75% of patients. Conclusion: All these results differ in some aspects when compared to other countries, which results from economic and social differences.